Hydrogen-terminated diamond MOSFETs on (0 0 1) single crystal diamond with state of the art high RF power density. Issue 1 (31st December 2022) - Yu, Cui; Zhou, Chuangjie; Guo, Jianchao; He, Zezhao; Ma, Mengyu; Yu, Hao; Song, Xubo; Bu, Aimin; Feng, Zhihong
Abstract: Diamond field-effect transistor (FET) has great application potential for high frequency and high power electronic devices. In this work, diamond FETs were fabricated on (0 0 1) single crystal diamond with homoepitaxial layer. The nitrogen impurity content in the homoepitaxial layer is greatly decreased as measured by the Raman and photoluminescence spectra. The diamond field effect transistor with 100 nm Al2 O3 as gate dielectric shows ohomic contact resistance of 35 Ω . mm, maximum drain saturation current density of 500 mA/mm, and maximum transconductance of 20.1 mS/mm. Due to the high quality of Al2 O3 gate dielectric and single crystal diamond substrate, the drain work voltage of −58 V is achieved for the diamond FETs. A continuous wave output power density of 4.2 W/mm at 2 GHz is obtained. The output power densities at 4 and 10 GHz are also improved and achieve 3.1 and 1.7 W/mm, respectively. This work shows the application potential of single crystal diamond for high frequency and high power electronic devices.